AN ANALYSIS OF THE IMPACT OF AI ON LEADERSHIP MANAGEMENT AND DECISION-MAKING PROCESSES - Irfan Maulana; Harlis Setiyowati (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the impact of the application of artificial intelligence (AI) on leadership management and decision-making processes in modern organizations, with a case study at PT. Oupu Building Materials, Tangerang. This study uses a qualitative descriptive approach through in-depth interviews with seven informants consisting of managers, division heads, and sales and promotion employees. The results show that the application of AI brings transformation in the decision-making process, where decisions become faster, more accurate, and data-driven. In addition, AI also changes the leadership style to be more collaborative and adaptive to technological developments. However, this study also identified several key challenges, such as dependence on data quality, the risk of algorithmic bias, and employee resistance to change. Leaders are required to develop ethical, adaptive leadership strategies oriented towards developing employees' digital competencies to maximize the potential of AI without neglecting the human aspect of decision-making. Thus, AI is not only an analytical tool, but also a catalyst in creating innovative.